The enlightenment against the Baroque : economics and aesthetics in the eighteenth century - Saisselin, Rémy G. (Rémy Gilbert), 1925- (University of California Press, 1992)
How do the seemingly disparate arenas of Enlightenment philosophy, economic theories, boudoir etiquette, literary styles, and artistic modes coincide in the late eighteenth century? In his poetic essay on the evolution of the idea of luxury and art, Remy Saisselin plots their intersection through precise, witty examples. Saisselin convincingly describes the development of our modern taste, ultimately the successor of the more spiritual and grand baroque taste. His analysis both illuminates and distinguishes between eighteenth-century and modern varieties of conspicuous consumption.
Keywords: Europe -- Civilization -- 18th century.; Civilization, Baroque.; Enlightenment.; Europe -- Civilisation -- 18e siècle.; Civilisation baroque.; Siècle des Lumières.; Enlightenment (18th-century western movement); HISTORY -- Europe -- Western.; Civilization; Civilization, Baroque; Enlightenment; Europe; 15.70 history of Europe.; Verlichting (cultuurgeschiedenis); Barok.; Economische filosofie.; Kunst.; Weelde.; Europe, Western -- Civilization -- 18th century.; 1700-1799